Pengaruh Pemberian Berbagai Konsentrasi Eco Enzyme Beberapa Kulit Buah Lunak Terhadap Pertumbuhan dan Hasil Tanaman Selada (Lactuca sativa L.) Varietas Grand Parid - Fadilah, Shinta Claudya; Azizah, Elia; Subardja, Vera Oktavia (JURNAL AGROPLASMA, 2025)
The low productivity of lettuce is caused by the declining quality of soil, both physically, chemically, and biologically. Improving production can be achieved through the proper application of organic fertilizers to enhance soil fertility. This study aimed to determine the effect of various concentrations of eco enzyme derived from soft fruit peels on the growth and yield of lettuce (Lactuca sativa L.) of the Grand Rapid variety. The research was conducted in February in Sukadami Village, South Cikarang District, Bekasi Regency. The method used was an experimental design arranged in a Completely Randomized Design (CRD) with a single factor, consisting of 8 treatments and 4 replications. The treatments included: C0 (control), C1 (2.5 ml/L), C2 (5 ml/L), C3 (7.5 ml/L), C4 (10 ml/L), C5 (12.5 ml/L), C6 (15 ml/L), and C7 (commercial eco enzyme at 10 ml/L). The results showed that the application of various eco enzyme concentrations did not significantly affect plant height, number of leaves, root length, or fresh plant weight based on the F-test at the 5% level. However, descriptively, treatment C6 (15 ml/L) produced the highest values across all parameters. The highest plant height at C6 was 9.43 cm (7 DAS), 15.70 cm (14 DAS), and 23.15 cm (21 DAS). The highest number of leaves was also observed in C6 at 13.86 leaves (28 DAS). Mean root length was 17.99 cm, fresh weight 36.14 g, leaf area 214.17 cm², and root weight 2.54 g. Eco enzyme at 15 ml/L showed potential to improve lettuce growth descriptively, although not statistically significant. Keywords: eco enzyme, soft fruit, lettuce